Hybrid Two Wheeler [HYBYK] - Purushothaman, T.; Srinivasan, V.; Francis Luther King, M. (International Journal of Psychosocial Rehabilitation, 2019)
Fuel consumption is one of the most important aspects that has to be noted before selecting any vehicle. Reduced usage of fuel with high efficiency is a characteristic of a good vehicle. With the increase in demand for fossil fuels, the need for a fuel-efficient two-wheeler has increased to a greater extent. Due to aspects such as cost and reliability, alternate fuels cannot replace fossil fuels completely. These efforts are mainly towards achieving a fuel-efficient two-wheeler, 'HYBYK,’ which uses both an IC engine and an electric drive. In a two-wheeler, while traveling a short distance, fuel consumption to power output ratio is comparatively less. Whereas an electric bike cannot travel longer distances but can cover short distances effectively. HYBYK combines these two properties and adds as an advantage. Since HYBYK has both an engine and an electric drive, short distances can be covered with the help of an electric drive and longer distances with a high fuel-to-power output ratio. Also, the system gets considerably charged while running. If fuel gets empty, an electric drive is there to lend a hand. Besides, there is a static solar power module that can be used to charge the battery. Thus, charging the battery becomes almost pollution-free. In a country like India where millions of people flock in traffic and waste fuel, HYBYK would serve better. Thus, with reasons such as reduced fuel consumption, less polluting, and economics, HYBYK would be a promising technology for a global green scenario.